High School Math Course-Taking: Shifts in Access and Achievement Post-COVID-19 - Megan Kuhfeld; Gustave Robinson; Jazmin Isaacs; Sofia Postell; Ji-Eun Lee; Erin Ottmar (AERA Open)
This study used NWEA’s MAP Growth math test scores from approximately 1.7 million students to examine the lasting effect of COVID-19 on high school math achievement and the associations among course-taking trajectories, demographic characteristics, and math achievement. We found that a drop in math achievement emerged for students in eighth grade in 2020–21 and persisted into 10th grade in spring 2023. Regarding students’ math course-taking trajectories, while there were no statistically significant COVID impacts on enrollment rates in Algebra 1, Geometry, and Algebra 2, significant negative COVID impacts were found for those who took these courses in 10th grade. Lastly, although pre-COVID disparities existed in math achievement across racial/ethnic subgroups, there were no disproportionate impacts of COVID-19 on specific racial/ethnic subgroups after controlling for prior achievement. Implications of these results for students’ math learning and school policies are discussed.